2021
DOI: 10.1186/s12883-021-02045-7
|View full text |Cite
|
Sign up to set email alerts
|

Systemic thromboembolism including multiple cerebral infarctions with middle cerebral artery occlusion caused by the progression of adenomyosis with benign gynecological tumor: a case report

Abstract: Background Adenomyosis, a benign gynecological disease, causes cerebral infarction. Similar to Trousseau’s syndrome, it elevates cancer antigen 125 (CA125) and D-dimer levels; causes hypercoagulability; and results in cerebral infarction. However, no case of adenomyosis causing major cerebral artery occlusion and requiring endovascular thrombectomy has yet been reported. We report on a woman with middle cerebral artery occlusion caused by adenomyosis progression with a benign gynecological tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Carcinoma mucins, including CA125 and CA19-9, promote thrombosis in Trousseau's syndrome by adhesion-dependent, bidirectional signaling in neutrophils and platelets ( 14 ). In previous reports, most adenomyosis patients with cerebral infarctions had high CA125 levels ( 1 - 9 ). In addition, several studies reported that CA19-9 levels were elevated in patients with adenomyosis who developed cerebral infarction ( 3 , 4 , 6 , 7 , 9 ).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Carcinoma mucins, including CA125 and CA19-9, promote thrombosis in Trousseau's syndrome by adhesion-dependent, bidirectional signaling in neutrophils and platelets ( 14 ). In previous reports, most adenomyosis patients with cerebral infarctions had high CA125 levels ( 1 - 9 ). In addition, several studies reported that CA19-9 levels were elevated in patients with adenomyosis who developed cerebral infarction ( 3 , 4 , 6 , 7 , 9 ).…”
Section: Discussionmentioning
confidence: 75%
“…In previous reports, most adenomyosis patients with cerebral infarctions had high CA125 levels ( 1 - 9 ). In addition, several studies reported that CA19-9 levels were elevated in patients with adenomyosis who developed cerebral infarction ( 3 , 4 , 6 , 7 , 9 ). In our case, CA125 and CA19-9 levels were slightly elevated, and pathological examination did not prove the overproduction of mucus.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…A laboratory examination revealed an elevated serum CA125 level (334.8 U/ml) (26). Aiura et al (27) reported the case of a 48-year-old woman with middle cerebral artery occlusion and recurrent cerebral infarction caused by adenomyosis progression. She was successfully treated with catheter-directed mechanical thrombectomy and by hysterectomy (27).…”
Section: Reviews Of the Literature On Adenomyosis-associated Thromboe...mentioning
confidence: 99%